A rare case of male infertility: Sertoli only syndrome - Babulreddy Hanmayyagari; Mounika Guntaka; Srinagesh (CHRISMED Journal of Health and Research, 2015)
Sertoli cell-only syndrome (SCOS) is not an uncommon finding in testicular biopsies that are performed in patients with infertility. The salient histopathologic feature of SCOS is the absence of germ cells. Many of these patients have a normal karyotype and normal secondary male sexual characteristics, yet are infertile and azoospermic or severe oligozoospermic. This case report describes a 29-year-old male patient who presented with primary infertility, normal physical characteristics and hormonal profile with SCOS detected on testicular biopsy.